Solvent-adaptable silver nanoparticles - Bhagavatula L. V. Prasad; Arumugam, S. K.; Bala, Tanushree; Sastry, M. (Langmuir, 2005)
A simple and efficient way of obtaining silver nanoparticles that are dispersible both in organic and in aqueous solvents using a single capping agent is described. The silver nanoparticles are initially prepared in water in the presence of aerosol OT [sodium bis(2-ethylhexyl)-sulfosuccinate, AOT]. Thereafter, transfer of the AOT-capped silver nanoparticles to an organic phase is induced by the addition of a small amount of orthophosphoric acid during shaking of the biphasic mixture. The AOT-stabilized silver nanoparticles could be separated out from the organic phase in the form of a powder. The hydrophobic nanoparticles thus prepared are stable and are readily resuspended in a variety of other polar (including water) and nonpolar solvents without further surface treatment. The amphiphatic nature of the silver surface is brought about by a small orientational change in the AOT monolayer on the silver surface in response to the polarity of the solvent.